Digitalisasi Pembelajaran Bahasa Indonesia Berintegrasi Pendidikan Karakter - Julianto, Indra Rasyid (Lembaga Yasin AlSys, 2023)
This article aims to analyze the integration of Indonesian language learning in schools that is related to language skills such as listening, speaking, reading, and writing with digitalization of learning that strengthens character education in students. Teachers have an important role in implementing character education to students. In this case, Indonesian language learning can be maximized with the variety of digital learning that can be utilized. In this case, teachers can maximize the basic competencies that can be integrated in strengthening character education can be narrowed down to religious values, national values, togetherness values, independence values, and integrity values. This article focuses on descriptive qualitative methods and literature studies from various relevant references regarding character education that can be integrated with Indonesian language learning at school. The results show that the basic competencies of class XI SMA can be integrated with the focused character education. Then, learning using digital technology can provide new things for teachers, students, and education units. This research focuses on the study of character integration by involving digitalization.